المعالم الفقهية للسيدة عائشة رضي الله عنها - شخمة منال; د/ شرقي خير الدين (جامعة عمار ثليجي الاغواط, 2023)
الملخص الحمد لله رب العالمين ، والعاقبة للمتقين والصلاة. السلام على عبده ورسوله و خليله وصفوته من خلقه نبينا وسيدنا محمد بن عبد الله ، وعلى آله وأصحابه ومن سلك سبيله واهتدى بهداه الي يوم الدين ، وبعد : ولما كان لُبُّ بحثي يخص أفقه نساء اهل الأرض ، وأحبهن الى قلب النبي (ﷺ) ، الصديقة بنت الصديق عائشة أم المؤمنين – رضي الله عنها – ، فتتناول هذه الدراسة ملامح من شخصيتها العلمية وقدرتها الإجتهادية في فهم نصوص الشريعة ، والطريقة الفقهية التي تميزت بها في صناعة الفتوى ، وتوضيح منهج الاسلام القويم في الاستدلال ، الذي يتميز باليسر ، ورفع الحرج ، ومراعاة مقاصد الشريعة كما أنه يمثل مادة دسمة في ترصد آراء السيدة عائشة في المسائل التي سَئلت عنها أو سُئلت عنها ، فغالبا ما كانت تعلق مستشهدة بما دار بينها وبين رسول الله (ﷺ) ، براعة السيدة عائشة وفكرها الواعي في الطرح يجعل الاستفادة منها عظيمة في حل مشكلات زمننا المعاصر ، خاصة وهي ناجمة عن سوء الفهم والتطبيق لسنة رسول الله (ﷺ) . Summary Praise be to God, Lord of the Two Worlds, and the end is for the righteous, and prayers and peace be upon His servant, His Messenger, his friend, and his elite among his creation, our Prophet and master, Muhammad bin Abdullah, and upon his family and companions, and whoever follows his path and is guided by his guidance until the Day of Judgment, and after: And since the core of my research concerns the horizons of the women of the people of the earth, and the most beloved of them to the heart of the Prophet (peace be upon him), the friend, the daughter of the friend, Aisha, the mother of the believers, may God be pleased with her, this study deals with features of her scientific personality and her diligent ability to understand the texts of Sharia, and the jurisprudential method that characterized her In making fatwas, and clarifying the method of correct Islam in reasoning, which is characterized by ease, removal of embarrassment, and observance of the purposes of Sharia. It also represents a wealth of material in monitoring the opinions of Mrs. Aisha in the issues that she was asked about or asked about, as she often commented citing what took place between her and the Messenger of God (peace be upon him). Our contemporary times, especially as they are caused by misunderstanding and application For the Sunnah of the Messenger of God (peace be upon him)